The Impact of the SQ3R Method on Physics Concept Understanding and Learning Outcomes in Measurement Material - Aini, Rohmatul; Koryataini, Lia; Suprianto, Suprianto; Hidayati, Nurul; Rihana, Rihana (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2024)
This study aims to evaluate the effectiveness of the SQ3R method in improving student learning outcomes and understanding of physics concepts related to measurements among class X-I students at SMA Negeri 3 Pamekasan. Conducted as classroom action research (CAR) with 36 participants, data were collected through a five-question test. Prior to implementing the SQ3R method, the average student score was 56.67, with a learning completion rate of 22.22%, indicating that 28 students had not achieved an adequate understanding of the material. Post-implementation, the average score increased to 75.28, with a learning completion rate of 61.11%, signifying successful comprehension for 22 students and an average improvement of 38.89%. In Cycle II, which focused on analyzing single and repeated measurements, the average score rose to 82.22, with an 86.11% completion rate, though five students (13.88%) remained below the required standard. Additionally, the SQ3R method positively impacted student engagement. In Cycle I, physical, mental, and emotional activities were recorded at 50.57%, 35.67%, and 61.11%, respectively. These metrics increased significantly in Cycle II to 86.27%, 92.24%, and 87%. These findings demonstrate the SQ3R method's effectiveness in enhancing learning outcomes, conceptual understanding, and student participation.